Evaluación nutricional y funcional de almidón de la fruta de pan (Artacarpus altilis)como potencial componente en alimentos, en la provincia de El Oro,2015. - Villaseñor Ortiz, David Andrés (2015)
Breadfruit (breadfruit) in major energy value and its starch content could be included in products with functional requirements regarding gastrointestinal health as dietary fiber, protein, resistant starches and β-glucans. The main objective of the study was to assess nutritional and functional starch breadfruit (breadfruit) isolated plantation in the province of El Oro. The study began by isolating the starch in the pilot plant Technical University of Machala, by the procedure set forth by (Bello-Pérez, A., 2000).